Birth companion satisfaction for the usage of Maathru Samman Pants while attending labor of their pregnant women as an initiative of respectful maternity care: A mixed method study - B Venkatashiva Reddy; Pulla Sirisha; Madhur Verma; Priti Gupta; Rakesh Kakkar; Star Pala; Wansalan Karu Shullai (Journal of Family Medicine and Primary Care)
Introduction: In India, having birth companions during labor and delivery has been increasingly recognized as an essential component of respectful maternity care. The present study was conducted to study birth companion satisfaction, acceptability, and demand for using Maathru Samman Pants (MSP) while attending labor of pregnant women in tertiary care health facilities. Methodology: Between 2023 and 2024, a multicentric study was conducted. For birth companion recruitment, tertiary care sites included District Hospital Tenali (South), District Hospital Bathinda (North), and District Hospital Shillong/NEIGRIHMS (East). The study utilized a mixed-method cross-sectional design with multistage, stratified, random sampling techniques based on the hospital’s delivery load. After the pregnant women delivered a baby using Maathru Samman Pants when the birth companion was comfortable answering the questions, an interview was carried out in the postnatal ward. The questionnaire was composed of 37 questions. Apart from the questionnaire, every 20th birth companion was also considered for qualitative data collection by taking in-depth interviews. Results: A total of 403 birth companions were studied. The majority (68.98%) of birth companions were between 41 and 60 years of age, followed by those aged 20–40 years (30.27%), and a small fraction over 60 years old (0.74%). Gender distribution was predominantly female, accounting for 99.5% of the total, with males representing only 0.5%. Most of the birth companions were mothers or mothers-in-law (81.14%), followed by sisters or sisters-in-law (14.64%). Of the total 50.62% agreed 38.96% strongly agreed that Maathru Samman Pants (MSPs) were comfortable during childbirth and 60.55% agreed it was comfortable for toilet use. Overall, MSP usage had high satisfaction scores among birth companions, particularly in the North and East. The overall usefulness of MSP was rated very highly, with an average score of 4.77 ± 0.54. A large majority (87.84%) of birth companions consider it extremely important to respect cultural norms during delivery. The importance of respecting cultural norms during delivery was rated very high among birth companions, with a mean score of 4.86 ± 0.42, particularly in the East (5.00). A significant majority (99.21%) of birth companions believe that the introduction of personalized delivery attire (MSP) is a positive initiative for respectful maternity care. Conclusion: The MSP has fostered a respectful and supportive birthing environment by maintaining privacy, offering comfort, and preventing unnecessary exposure. The high satisfaction, acceptability, and demand for MSP of birth companions across regions highlight its cultural sensitivity and appropriateness. Government healthcare facilities should adopt the MSP universally to enhance the childbirth experience for women and birth companions.